Four Pedotransfer functions for estimating soil water retention in soils: Performance evaluation and implications for water resources management - Hidalgo-Campos, Carlos Manuel (2025)
Introduction. Technical, economic, and efficient management of natural resources such as soil and water is fundamental and imperative to ensure sustainable agricultural production. Pedotransfer functions (PTFs) are tools for estimating soil hydrological properties, such as water retention, from other easily measurable soil variables. Objective. To evaluate the performance of four functions in estimating soil water content at two reference points field capacity (FC) and permanent wilting point (PWP) in Costa Rican soils. Methodology. Using soil profile data available for Costa Rica, the fitting parameters of the van Genuchten equation were estimated to calculate soil water content (θ) at FC and PWP through two functions: Rosetta1 and Rosetta3. These values were also derived using the empirical equations of Peele and Briggs. The estimated data were compared with laboratory measurements, and predictive performance indices were calculated to assess the accuracy of the functions. Results. The empirical equations of Peele and Briggs exhibited very poor performance in estimating soil water content at FC and PWP. In contrast, Rosetta1 and Rosetta3 demonstrated good performance in estimating the van Genuchten parameters. Nevertheless, considerable deviations between FC and PW7 measured and estimated values were observed, particularly in Andisols. Conclusion. Caution is advised when applying Rosetta1 and Rosetta3 for soil water content estimation, as inaccuracies may affect the appropriate management of soil and water resources. The use of Peele and Briggs’ empirical equations is not recommended for irrigation scheduling.